Multimedia Interaktif Berbasis Pendekatan Konteksual Materi Pecahan Efektif digunakan dalam Pembelajaran Matematika di Sekolah Dasar - Ni Kadek Ria Oktaviani; I Wayan Wiarta; Dewa Gede Firstia Wirabrata (Jurnal Media dan Teknologi Pendidikan, 2025)
The background of this research indicates a lack of innovative learning media and contextual approaches in mathematics education, resulting in monotonous teaching that negatively impacts students' learning outcomes. The aim of this study is to analyze the effectiveness of interactive multimedia based on a contextual approach for the topic of equivalent fractions. The research model used is the ADDIE development model, with subjects comprising 39 fourth-grade students. The results of this study are very promising. The design review by experts received an excellent rating, and the feasibility testing indicates that the interactive multimedia based on the contextual approach is suitable for use in teaching. This is based on: the content/material review by experts rated as very good, the instructional design review rated as very good, the media review rated as very good, the individual trial rated as very good, and the small group trial rated as very good. Furthermore, the effectiveness test yielded a tvalue of 14.046 and a critical tvalue of 1.686, indicating that tvalue ≥ critical tvalue (14.046 ≥ 1.686), which means that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Therefore, it can be concluded that the interactive multimedia based on a contextual approach is effective for use in mathematics learning with the topic of equivalent fractions in fourth-grade elementary school.